Economic and environmental nitrate leaching consequences of 4R nitrogen management practices including use of inhibitors for corn production in Ontario. (15th December 2021) - De Laporte, By Aaron; Banger, Kamaljit; Weersink, Alfons; Wagner-Riddle, Claudia; Grant, Brian; Smith, Ward
Abstract: Nitrate (NO3 − ) leaching has negative human and environmental health consequences that can be attributed to and mitigated by agricultural decision making. The purpose of this study is to examine the economic and environmental nitrogen (N) leaching reduction from 4R (Right Rate, Right Source, Right Time, Right Placement) agricultural management practices, including application methods, timing and rates, and the use of nitrification and urease inhibitors, for Ontario corn production. This study employed an integrated biophysical and economic GIS-based simulation model considering corn yields, prices, and production costs, and environmental losses, under historical weather scenarios, with NO3 − leaching constraints. Reducing N application from historical to model optimized agronomic rates sharply lowered corn NO3 − leaching from 75.3 to 24.9 kt N per year. Increasing model restrictions on corn NO3 − leaching increased the use of broadcast and sidedress application methods compared to injection and lower overall production. They also increased the use of nitrification and urease inhibitors, which increased N use efficiency, because they allowed lower leaching from corn production, for a price. Leaching decreases from restrictions trade-off with ammonia (NH3 ) volatilization increases, but there was no trade-off with nitrous oxide (N2 O) emissions. This highlighted the importance of considering net N losses and production trade-offs by policy decision-makers when developing N loss reduction strategies. Highlights: Optimized agronomic N rates increase profit and decrease NO3 − leaching losses. NO3 − constraints increase the use of nitrification and urease inhibitors. NO3 − leaching decreases trade-off with NH3 volatilization increases. 4R placement, timing, and source have a role but right rate is more effective.